The relationship between social media use, eating attitude and body mass index among nutrition and dietetic female students: A cross-sectional study - KARĞIN, DİCLE; GÜNEŞ, FATMA ESRA; AKTAÇ, ŞULE (ASOC ESPANOLA DIETISTAS NUTRICIONISTAS, 2021)
Introduction: This study aimed to investigate the relationship between media using habits, frequency and duration, and body mass index on eating attitudes. Material and Methods: The cross-sectional study was conducted with female students who received nutrition and dietetics education in Istanbul. A questionnaire consisting of a socio-demographic questionnaire, Eating Attitude Test (EAT-40), and Social Media Attitude Scale was applied to 1248 female volunteers by the face-to-face interview method. Results: It was found that 35.7% of the participants had abnormal eating attitudes and 89.6% showed a positive attitude towards social media. 93.7% of the group with abnormal eating attitudes indicated a positive attitude towards social media, 0.4% had a negative attitude and the difference was statistically significant (p=0.001). It was observed that a significant difference between EAT-40 and thought of an eating problem, having a social media membership, and spending time on social media (p<0.05). Conclusions: Social media have an effect on nutrition dietetics students on abnormal eating attitude; it did not show a significant effect on BMI.
Keywords: Body Mass Index; Feeding Behavior; Social Media; Female; Students; Universities